1993
DOI: 10.1002/adma.19930050214
|View full text |Cite
|
Sign up to set email alerts
|

Optically transparent nanometal composite membranes

Abstract: Small metal particles embedded in an optically transparent matrix result in a composite material which can be transparent in the infrared and into the visible (metals are usually optically opaque). The nanoparticles of the metal are produced by the “template” method, where the material is synthesized within the pores of a nanoporous membrane (see Figure). magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 8 publications
0
38
0
Order By: Relevance
“…The membranes 3 prepared in that study had much smaller pores (co. 50 nm in diameter), and the resulting particles showed extinction maxima in the visible spectrum reminiscent of aqueous gold colloids of similar size. In that work, we demonstrated how the template synthesis approach allows for simple control of gold nanocylinder aspect ratio and that varying the particle aspect ratio gives rise to systematic shifts in the extinction max-imum [10]. We also showed that the observed effects of particle shape are qualitatively consistent with the predictions of MaxwellGarnett Theory (M-G), which is a simple treatment for composite materials that addresses particle shape and orientation but not size [111.…”
Section: Introductionmentioning
confidence: 70%
“…The membranes 3 prepared in that study had much smaller pores (co. 50 nm in diameter), and the resulting particles showed extinction maxima in the visible spectrum reminiscent of aqueous gold colloids of similar size. In that work, we demonstrated how the template synthesis approach allows for simple control of gold nanocylinder aspect ratio and that varying the particle aspect ratio gives rise to systematic shifts in the extinction max-imum [10]. We also showed that the observed effects of particle shape are qualitatively consistent with the predictions of MaxwellGarnett Theory (M-G), which is a simple treatment for composite materials that addresses particle shape and orientation but not size [111.…”
Section: Introductionmentioning
confidence: 70%
“…The alumina template membranes were prepared electrochemically from Al metal [9,10]. The details of the membrane syntheses will be given in [10].…”
Section: Number Of Pagesmentioning
confidence: 99%
“…The details of the membrane syntheses will be given in [10]. These membranes contain cylindrical pores of uniform diameter [8][9][10]. Membranes with pore diameters of 50 nm were prepared for these studies.…”
Section: Number Of Pagesmentioning
confidence: 99%
See 1 more Smart Citation
“…SPRs not only contribute to stronger molecularoptical interactions on roughened films, i.e., irregularly shaped surfaces, but they also play a role in the unique properties and enhanced absorption of molecules on regular metallic structures, such as meshes that exhibit extraordinary transmission due to traveling SPRs. [28][29][30][31][32] Other interesting effects in the optical properties of metal nanoparticles include their transparency 3,33,34 and enhanced optical absorption and fluorescence. [35][36][37] There has also been significant interest in the electron dynamics of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%